The Relationship Between Clinical Manifestation and Histopatological Result in Non- Hodgkin Lymphoma: RSUD Dr. Soetomo Surabaya - Glazydia Juwita Rachma; Ugroseno Yudho Bintoro; Mia Ratwita Andarsini; Novira Widajanti (Health Notions, 2021)
Non-Hodgkin's lymphoma is a major public health problem with over 14.1 million people are diagnosed with it (2012). In the same year there were 8.2 million deaths due to cancer. The purpose of this study was to determine the relationship between clinical manifestations and the degree of malignancy based on histopathological features in patients with Non-Hodgkin's Lymphoma. This study used a retrospective analytical method with a cross-sectional approach using the patient's medical record at RSUD Dr. Soetomo, Surabaya who was diagnosed with Non-Hodgkin Lymphoma from 1st January 2015 to 31st December 2017. In this study, there were 139 samples include those criteria, with a greater number of male samples (62.6%) compared to women (37.4%). This study showed that 49.3% of patients with non- Hodgkin's lymphoma in RSUD Dr. Soetomo with clinical manifestations without symptoms actually experience malignancy with a high degree, this showed that clinical manifestations without symptoms are not always associated with a low level of malignancy. Then, based on the Chi Square test results obtained p-value of 0.289 (>0.05), so there was no significant relationship between clinical manifestations and the degree of malignancy. Keywords: lymphoma; manifestation; histopatological